Giuliana Ancidei, Notas para la biografía del padre jesuita y poeta latino Alejandro Rapicani, México, U.N.A.M., 1996, 69 pp. (Minerva, 2019)
Review: Giuliana Ancidei, Notas para la biografía del padre jesuita y poeta latino Alejandro Rapicani, México, U.N.A.M., 1996, 69 pp.